2016
DOI: 10.2298/hemind151119008l
|View full text |Cite
|
Sign up to set email alerts
|

Determination of essential and toxic elements in products of milling wheat

Abstract: In the production bread wheat bran is used as a raw material rich in dietary fiber. Therefore, it is necessary to monitor the content of essential and toxic elements in the flour and bran. This paper investigates essential (Zn, Cu, Fe and Mn) and toxic (Pb, Cd, Hg and As) elements in products of milling wheat grown in the whole territory of Banat, the region in Serbia. Inductively Coupled Plasma Mass Spectrometry was used for analysis. The mean contents of the following elements Pb, Cd, Hg, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Ludajić et al. [ 23 ], reported Zn concentration in the bran is higher 11 times than in the flour. This is in agreement with what is observed by Tóth [ 17 ], who showed Zn concentration varied in the range from 17.6 to 33.7 mg/kg in wheat grains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ludajić et al. [ 23 ], reported Zn concentration in the bran is higher 11 times than in the flour. This is in agreement with what is observed by Tóth [ 17 ], who showed Zn concentration varied in the range from 17.6 to 33.7 mg/kg in wheat grains.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, the content of Fe, as the second metal in Sweden's wheat flour and wheat bran, was found between 12.4 and 240.4 mg/kg in bran and 6.76–20.1 mg/kg in wheat flour. Also, a significant reduction of Fe was observed [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Grembecka et al [ 60 ] recounted that 100 g of bread supplied 9.57–20% RDA Fe and 5.41–15.3% RDA Zn to an adult Pole, depending on the type of bread (more in the case of whole meal bread). Studies carried out in Serbia revealed that bread and baked goods covered 10–22% of the daily requirement of Zn, 11–30% of Cu, and 17–37% of Fe [ 61 ]. UK studies showed that two slices of bread cover 14% of the daily requirement of Zn for women and 11% for men [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Wheat grain is a prominent source of various mineral elements (Cu, Zn, Fe, Ni, and Mn) that are important for both plants and humans, which could be essential, but also toxic in higher concentrations. Wheat grain also contains several toxic elements, such as As, Pb, Hg, and Cd [8]. Therefore, the focus on winter wheat production, besides availability, is shifted to the chemical composition and methods to improve it.…”
Section: Introductionmentioning
confidence: 99%